Immunocytochemical studies of quaking mice support a role for the myelin-associated glycoprotein in forming and maintaining the periaxonal space and periaxonal cytoplasmic collar of myelinating Schwann cells (The Rockefeller University Press, 1984)
The myelin-associated glycoprotein (MAG) is an integral membrane glycoprotein that is located in the periaxonal membrane of myelin- forming Schwann cells. On the basis of this localization, it has been hypothesized that MAG plays a structural role in (a) forming and maintaining contact between myelinating Schwann cells and the axon (the 12-14-nm periaxonal space) and (b) maintaining the Schwann cell periaxonal cytoplasmic collar of myelinated fibers. To test this hypothesis, we have determined the immunocytochemical localization of MAG in the L4 ventral roots from 11-mo-old quaking mice. These roots display various stages in the association of remyelinating Schwann cells with axons, and abnormalities including loss of the Schwann cell periaxonal cytoplasmic collar and dilation of the periaxonal space of myelinated fibers. Therefore, this mutant provides distinct opportunities to observe the relationships between MAG and (a) the formation of the periaxonal space during remyelination and (b) the maintenance of the periaxonal space and Schwann cell periaxonal cytoplasmic collar in myelinated fibers. During association of remyelinating Schwann cells and axons, MAG was detected in Schwann cell adaxonal membranes that apposed the axolemma by 12-14 nm. Schwann cell plasma membranes separated from the axolemma by distances greater than 12-14 nm did not react with MAG antiserum. MAG was present in adaxonal Schwann cell membranes that apposed the axolemma by 12-14 nm but only partially surrounded the axon and, therefore, may be actively involved in the ensheathment of axons by remyelinating Schwann cells. To test the dual role of MAG in maintaining the periaxonal space and Schwann cell periaxonal cytoplasmic collar of myelinated fibers, we determined the immunocytochemical localization of MAG in myelinated quaking fibers that displayed pathological alterations of these structures. Where Schwann cell periaxonal membranes were not stained by MAG antiserum, the cytoplasmic side of the periaxonal membrane was "fused" with the cytoplasmic side of the inner compact myelin lamella and formed a major dense line. This loss of MAG and the Schwann cell periaxonal cytoplasmic collar usually resulted in enlargement of the 12-14-nm periaxonal space and ruffling of the apposing axolemma. In myelinated fibers, there was a strict correlation between the presence of MAG in the Schwann cell periaxonal membrane and (a) maintenance of the 12-14- nm periaxonal space, and (b) presence of the Schwann cell periaxonal cytoplasmic collar.(ABSTRACT TRUNCATED AT 400 WORDS)